PERANCANGAN SUPERVISORY CONTROL AND DATA ACQUISITION (SCADA) MENGGUNAKAN SOFTWARE CX-SUPERVISOR 3.1 PADA SIMULASI SISTEM LISTRIK REDUNDANT BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) OMRON CP1E NA-20-DRA - Almuhtarom, Almuhtarom; Sasmoko, Priyo (Gema Teknologi, 2015)
Almuhtarom, Priyo Sasmoko, in this paper explain that the existence of electrical energy for human needs can not be separated, the electrical energy used by all humans on this planet of small-scale (household) to large-scale industry. Demand the amount of electrical energy and the quality of the electricity transmission system has increased over time. Disruptions in electricity transmission system could be fatal for the electrical components or the operating loss in an industry. SCADA is proposed to accommodate this problem. SCADA is able to monitor and control the disturbances in electrical systems redundant. The purpose of this final project is to simulate a SCADA system to eliminate redundant electric power transmission network failures such as open-circuit, short circuit, and overload that can be controlled directly from the plant or via an interface on the computer. Ladder diagram programming languages ​​used to design the PLC system. Hardware and software to support this thesis, such as plant redundant electrical systems, Omron PLC CP1E NA-20-DRA, Laptop, CX One 9.3 software for programming the PLC and the CX Supervisor 3.1 for building HMI. The test results indicate that the current sensor can be used to detect if an interruption occurs in the form of overload and short circuit simulate disturbances. Plant redundant electrical system can be monitored and controlled through input-output of the plant, computer interface, and the World Wide Web. There is a relay on a plant that can connect to the electricity grid cut power lines when an interruption occurs. If an interruption occurs in the form of an open circuit, short circuit or overload, alarm and disturbance indicators will be active. Keywords: SCADA, PLC, open circuit, short circuit, overload